Information security : - LeVeque, Vincent (Wiley, 2006)
This must read for enterprise (security) planning describes how to fit information security into the long-term business vision for an enterprise by incorporating information security into a general enterprise strategic planning framework, and by defining information security as 'best practice' management of information assets (data and systems for managing data).